Korelasi Spasial Temporal Hotspot dengan Parameter Meteorologi - Adilaksa Kharisma; Fransisco Jordan Nathaniel Darisman Siahaan; Yuane Anike Aiboy (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
The threat of forest fires in Indonesia can be effectively monitored through the detection of hotspots identified via MODIS Terra/Aqua satellite observations. East Nusa Tenggara Province (NTT) has been recognized as a region experiencing significant forest fire activity from 2019 to 2023. A comprehensive study examining the correlation between hotspot frequency and meteorological parameters is essential to elaborate the relationship between these variables. Spatial distribution analysis of hotspot data, utilizing the kernel density estimation method, has been employed to map areas with high densities of hotspot occurrences. The findings indicate that Kupang Regency, Alor Regency, Lembata Regency, and North Central Timor Regency exhibit a higher density of hotspot compared to other regions. Seasonal distribution analysis reveals a tendency for increased hotspot occurrences during the dry season. Pearson correlation analysis on spatial and temporal correlations indicates that the relative humidity parameter exhibits the strongest correlation, with a temporal correlation coefficient of -0.359 and a spatial correlation range of -0.4 to -0.5. This spatial correlation enhances the understanding of weather patterns associated with hotspot occurrences. Overall, the correlation values between hotspot frequency and meteorological parameters exhibit variability, facilitating improved monitoring of hotspot occurrences in relation to prevailing weather and climate conditions.